1991
DOI: 10.1111/j.1365-2478.1991.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

SEISMO‐ELECTRIC EXPLORATION: EXPECTED SIGNAL AMPLITUDES1

Abstract: For more than 20 years, Soviet scientists have published papers and registered patents describing the conversion of seismic to electromagnetic energy in geological environments and the detection of the electric or magnetic signals as a method of geophysical exploration. Because of the potential importance of a reliable geophysical technique for locating quartz veins, we have been conducting extensive laboratory and field tests of the phenomena. For the purposes of designing appropriate field tests we need to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Pride & Haartsen 1996;Haartsen & Pride 1997;Garambois & Dietrich 2001, 2002Ren et al 2012;Gao et al 2013a,b), motional induction (e.g. Gershenzon et al 1993 & Barker 1991;Ogawa & Utada 2000a,b). However, these studies have not covered the entire possible range of EM sources in the Earth's crust; thus, studies of unconsidered mechanisms are still required to fully characterize elastic-EM conversions due to seismic waves.…”
Section: Introductionmentioning
confidence: 99%
“…Pride & Haartsen 1996;Haartsen & Pride 1997;Garambois & Dietrich 2001, 2002Ren et al 2012;Gao et al 2013a,b), motional induction (e.g. Gershenzon et al 1993 & Barker 1991;Ogawa & Utada 2000a,b). However, these studies have not covered the entire possible range of EM sources in the Earth's crust; thus, studies of unconsidered mechanisms are still required to fully characterize elastic-EM conversions due to seismic waves.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have demonstrated electrokinetic effects in porous media (Kozak and Davis, 1987;Neev and Yeatts, 1989;Thompson and Gist, 1991;Pride and Morgan, 1991;Pride et al, 1993;Haartsen, 1995). Field tests have also observed seismoelectric effects (Martner and Sparks, 1959;Sobolev et aI., 1984;Russell and Barker, 1991;Thompson and Gist, 1993). Because of the low signalto-noise ratio in field tests, intensive data processing is needed to extract the electric signals; it is difficult to compare the field results to the theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…As for the prospecting of mineral piezoelectric crystals, Kepic et al (1995) estimated the distribution of sulfide minerals by simultaneous measurement of the acoustic wave and the electric field during an explosion experiment, which indicated that in-situ electric signal detection is possible under a special condition. Russell and Barker (1991) also numerically estimated amplitude of seismo-electric signal presuming a piezoelectric sphere embedded under the ground, expected in seismo-electric exploration. It showed consistency between amplitudes of the observed and expected piezoelectric signals.…”
Section: Introductionmentioning
confidence: 99%